HAK-HAK NORMATIF PEKERJA PADA PERUSAHAAN YANG DINYATAKAN PAILIT - Wisnu Yoga Wijaya, I Made; Wiratni Darmadi, A. A. Sagung; Dharma Kusuma, A. A. Gede Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 08, September 2013, 2013)
The title of this legal research is employee normative rights of bankrupt company. Employee normative rights is a basic rights of employee in employment relationship that protected and guaranteed by the statute. There are several classifications of employee normative rights, such as economical rights; political rights; medical rights; and social rights. When a company was declared bankrupt, the company frequently does not fulfill the employee normative rights. The aim on this paper is to determine the employee normative rights at a bankrupt company. The research method used in this paper is the normative legal research using legal materials collection techniques of literature. The result obtained from this research show that employee normative rights is the precedence debt payment, because the employee normative rights is one of the basic human rights, which is the fulfillment can not be reduced under any circumstances.
Keywords: Normative Rights, Company, Bankrupt